2014
DOI: 10.21149/spm.v56i1.7321
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades psicométricas del Cuestionario Maltrato en el Noviazgo en una muestra de mujeres estudiantes mexicanas de nivel medio superior y superior

Abstract: Objetivo. Modificar y adaptar el Cuestionario Maltrato en el Noviazgo (CMN), versión binacional Italia-México, a una muestra de mujeres estudiantes de nivel medio superior y superior del Distrito Federal y del Estado de México. Material y métodos. Estudio transversal en el que participaron 2157 estudiantes de edades entre 14 y 33 años. Los reactivos se analizaron mediante el método elemento-escala; se aplicó un análisis factorial confirmatorio. Resultados. El CMN mostró una consistencia interna de α=0.95; el a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Regarding the sex of the participants, violence was analysed in women in only six of the studies (Al‐Modallal et al, 2020; Anderson & Leigh, 2010; Começanha & Maia, 2018; Follingstad et al, 2015; Osorio‐Guzmán, 2014; Wong et al, 2018) while the rest addressed both sexs (62.6%). Only seven studies (20%) reported non‐binary gender and other forms of non‐heteronormative sexual orientation (Bledsoe & Sar, 2011; Borrajo et al, 2015; Demirtas et al, 2018; Emelianchik‐Key et al, 2018; Morelli et al, 2018; Rothman et al, 2021; Soriano‐Ayala et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the sex of the participants, violence was analysed in women in only six of the studies (Al‐Modallal et al, 2020; Anderson & Leigh, 2010; Começanha & Maia, 2018; Follingstad et al, 2015; Osorio‐Guzmán, 2014; Wong et al, 2018) while the rest addressed both sexs (62.6%). Only seven studies (20%) reported non‐binary gender and other forms of non‐heteronormative sexual orientation (Bledsoe & Sar, 2011; Borrajo et al, 2015; Demirtas et al, 2018; Emelianchik‐Key et al, 2018; Morelli et al, 2018; Rothman et al, 2021; Soriano‐Ayala et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 studies that showed validations of instruments in different languages and/or cultures, only 5 studies (Aizpitarte et al, 2017; Demirtas et al, 2018; Lara & López‐Cepero, 2021; Osorio‐Guzmán, 2014; Wong et al, 2018) complied with all the aspects of the standards set out in Guidelines for the process of cross‐cultural adaptation of self‐report measures (Beaton et al, 2000), necessary in PROM development. These five studies showed a forward translation–back translation method by several translators independently, consulted experts in the field of interest and cognitive interviews with the target population, adapting to the standards described above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 10 studies, seven cross-culturally adapted questionnaires as well as validations were analyzed: AADS 46,47 ; CAD-RI 46,[48][49][50] ; CTS2 51 ; CUVINO 52,53 ; JVCT 47 ; M-CTS 54 and PAJ 55 . Three articles analyzed the measurement properties of three questionnaires, CADRI, CMN and VEC Scale [56][57][58] , and two observational studies refer to the measurement properties of two questionnaires, CVPU and Checklist of Experiences of Partner Abuse 59,60 .…”
Section: Resultsmentioning
confidence: 99%
“…
This article evaluated the effects of an interpersonal skills program based on artistic expressions to reduce intimate partner violence in college students. The research was of explanatory type, quasi-experimental design and used the Dating Abuse questionnaire (adapted by Osorio, 2014), the Interpersonal Skills questionnaire with reliability of 0.81 having as results in the entry test in terms of violence a mean of 88. 16 and after the program was applied it decreased to 81.2, in interpersonal skills the mean of 46.6 increased to 53.3 with large effect size according to , statistically significant differences were found in terms of violence
…”
mentioning
confidence: 99%